Функція внутрішньої події в «Записках Тані М.» Галини Гордасевич - Шахова, Катерина; Shakhova, Kateryna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядається функція внутрішньої події в «Записках Тані М.» Галини Гордасевич у ракурсі поетикальних особливостей записок як жанрового різновиду української прози. Визначено специфіку нара-тивного розгортання внутрішньої події в записках на прикладі аналізованого твору. The article deals with the function of inner (psychological) state in «Tanya M.’s Notes» by Halyna Hordasevych in the perspective of notes poetics features studying as the Ukrainian prose genre variety. Notes are not profound explored genre in Ukrainian literary criticism. In the Ukrainian writers works of the ХХ – beginning of the XXI centuries are presented by «Сaptive’s Notes» by O. Kobets, «Soldier’s Notes» by I. Bahmut, «Tanya M.’s Notes» by H. Hordasevych, «White Bird’s Notes» by H. Pahutiak, «Notes of Ukrainian samashedshy» by L. Kostenko and others. Notes genre is characterized by amplitude fluctuation between the documentary and art principles, which depends on the author’s writing intentions. «Tanya M.’s Notes» by Halyna Hordasevych is purely artistic work, which include important element of poetics, that is an event. It determines writing by the main character, Tanya, notes, where the narrator’s inner world is the object of self-representation. Notes focus recipient on the dynamics of author’s thoughts and feelings, character changes as the result of spiritual experience in private life. Psychological states in «Tanya M.’s Notes» are the key moments, that determine action development and show the essential features of main character’s world outlook.
The Inner State in «Tanya M.’s Notes» by Halyna Hordasevych
Keywords: записки; повість; внутрішня подія; оповідач; наратив; notes; story; inner state; narrator; narrative